Genomic Investigation of Infantile and Childhood Epileptic Encephalopathies in Kazakhstan: An Urgent Priority - Jaxybayeva, Altynshash; Nauryzbayeva, Alissa; Khamzina, Assem; Takhanova, Meruert; Abilhadirova, Assel; Rybalko, Anastasia; Jamanbekova, Kymbat (Frontiers in Neurology, 2021)
Objectives: Infantile and childhood epileptic encephalopathies are a group of severe epilepsies that begin within the first year of life and often portend increased morbidity. Many of them are genetically determined. The medical strategy for their management depends on the genetic cause. There are no facilities for genetic testing of children in Kazakhstan but we have a collection of data with already defined genes responsible for clinical presentations. Methods: We analyzed children with epileptic enchephalopathies that began in the first 3 years of life and were accompanied by a delay/arrest of intellectual development, in the absence of structural changes in the brain. Such patients were recommended to undergo genetic testing using epileptic genetic panels in laboratories in different countries. Results: We observed 350 infants with clinical presentation of epileptic encephalopathies. 4.3% of them followed our recommendations and underwent genetic testing privately. In total 12/15 children became eligible for targeted treatment, 3/15 were likely to have non epileptic stereotypies / movements, 2/15 were unlikely to respond to any therapy and all had a high chance of intellectual disability, behavioral and social communication disorders. Conclusion: The genetic results of 15/350 (4.3% of patients) have demonstrated the potential and enormous impact from gene panel analysis in management of epileptic encephalopathy. Availability of genetic testing within the country will improve management of children with genetic epilepsies and help to create a local database of pathogenic variants